Dryland Ecohydrology: Research Perspectives - Odorico, Paolo D; Scanlon, Todd M; Runyan, Christiane W; Abshire, Kate; Barrett, Patrick; Bhattachan, Abinnash; Coloso, James J; Erler, Ashton; Miller, Janet; Mitchell, Nathan; Mobley, John; Vleet, Diana Van; et al. (Annals of Arid Zone, 2016)
Water is an essential resource for life on earth and all living organisms depend , onit.Thebiota,in turn, affectsthedynamicsofmajorhydrologicalprocesses,therebydetermining the rate of the water cycle.Researchin ecohydrologyfocuseson interactionsbetweenecological and hydrologicalprocesses.These interactionsare particularlystrong in the case of dryland ecosystems,where water availabilityis the main limiting factor to vegetation dynamics and ecosystemprimary production.Thispaper providesa reviewof the main hydrologicalprocesses affecting ecosystem dynamics, as well as of the ecologicalprocesses controlling the water cycle on the earth. Key words: Ecohydrology,drylands, plant water stress, soil moisture, ecogeomorphology